EU-China relations in a post-COVID-19 world order: the context of the BRI project - Downes, James F.; Lai, Kenneth (Frontiers in Political Science, 2025)
IntroductionThe evolving relationship between the European Union (EU) and China has become a defining feature of global geopolitical dynamics in the post-COVID-19 era. This paper examines shifts in EU-China relations since 2013, focusing on the impact of China’s Belt and Road Initiative (BRI) in the context of broader international developments, including the COVID-19 pandemic, geopolitical crises, and shifting strategic priorities.MethodsA multi-method qualitative approach is employed, incorporating comparative case studies of four countries (Germany, Hungary, Italy, and Serbia) alongside descriptive analysis of trade, investment, and participation data from 2013 to 2024. Statistical data from Eurostat and other sources are used to complement qualitative insights on economic and political trends shaping EU-China interactions.ResultsFindings reveal a significant transformation in the trajectory of EU-China relations. The COVID-19 pandemic acted as a critical juncture, accelerating a shift from pragmatic economic cooperation toward heightened strategic caution and risk aversion. While China’s BRI facilitated development opportunities, particularly in Central and Eastern Europe, divergent political and economic interests across EU member states led to varied engagement levels. Germany and Italy adopted cautious, economic-first approaches, while Hungary and Serbia pursued deeper ties with China amid democratic backsliding and strategic ambiguity. Trade between the EU and China expanded during the BRI era, with imports from China increasing notably during the pandemic, although trade imbalances persist. The EU’s internal divisions and the intensifying US-China rivalry complicate cohesive EU strategies toward China.DiscussionThe complex interplay of ideological divergence, security concerns, and domestic political factors result in a fragmented and ambivalent EU-China relationship. The BRI’s uneven uptake across Europe reflects both China’s targeted geopolitical strategy and the EU’s multi-level governance challenges. The emerging post-pandemic world order is marked by strategic competition intertwined with economic interdependence, requiring nuanced diplomatic balancing by European actors. This analysis underscores the need for differentiated policy responses within the EU and highlights ongoing shifts in global power structures influenced by China’s expanding global role.